Genç Üniversite Öğrencilerinin Girişimcilik Niyeti üzerinde Planlı Davranış Teorisi ile birlikte Fırsatları Görme ve Teşvik Desteğinin Etkisi - Tuygun Toklu, Arzu (Muş Alparslan Üniversitesi, 2020)
Entrepreneurship is related to the current difficulties and the ability to foresee the opportunities that situation creates. Entrepreneurial individuals not only do a business for themselves, but they also bring about creativity and innovation by creating value for society. The aim of this study is to investigate the effect of incentive support provided to individuals who are studying in university. In addition to financial support, the research focuses on the effects of seeing opportunities, personal attitude towards entrepreneurial behaviour, perceived behavioural control, and subjective norm on individuals'entrepreneurial intention. The data used for the research were selected by using convenience sampling method among the second year students who have not taken the entrepreneurship course in the School of Applied Sciences. The data collected by using web-based survey were analysed using SPSS v23 statistical program and SmartPLS structural equation modelling. According to the findings obtained from the study, it was found that financial opportunities with personal attitude towards entrepreneurship behaviour and perceived behavioural control had an effect, while there was no effect with seeing opportunities and subjective norm on entrepreneurial intention. Having entrepreneurship point of views in universities for entrepreneurship that can be developed through education and training is considered to be an added value in the development of the country.

The aim of the study is to investigate the effect of incentive support provided to individuals who are studying in university. In addition to financial support, the research focuses on the effects of seeing opportunities, personal attitude towards entrepreneurial behavior, perceived behavioral control, and subjective norm on individuals'entrepreneurial intention. The data were selected by using convenience sampling method among the second year students who were not taken the entrepreneurship course in the School of Applied Sciences. The data collected by using web-based survey were analyzed using SPSS v23 and SmartPLS SEM. According to the findings, financial opportunities with personal attitude towards entrepreneurship behavior and perceived behavioral control have effects, while there are no effects with seeing opportunities and subjective norm on entrepreneurial intention. Having entrepreneurship point of views in universities for entrepreneurship that can be improved through education and training is considered to be an added value in the development of the country.
The Impact of Seeing Opportunities and Incentive Support with the Theory of Planned Behaviour on Entrepreneurial Intention of Young University Students
anemon
Keywords: Entrepreneurial Intention; Theory of Planned Behaviour; Seeing Opportunities; Incentive Support; Girişimcilik Niyeti; Planlı Davranış Teorisi; Fırsatları Görme; Teşvik Desteği